Alzheimer’s polygenic risk scores, APOE, Alzheimer’s disease risk, and dementia-related blood biomarker levels in a population-based cohort study followed over 17 years - Stocker, Hannah; Trares, Kira; Beyer, Léon; Perna, Laura; Rujescu, Dan; Holleczek, Bernd; Beyreuther, Konrad; Gerwert, Klaus; Schöttker, Ben; Brenner, Hermann (Alzheimer's research & therapy, 2023)
In order to utilize polygenic risk scores (PRSs) for Alzheimer’s disease (AD) in a meaningful way, influential factors (i.e. training set) and prediction across groups such as APOE e4 (APOE4) genotype as well as associations to dementia-related biomarkers should be explored. Therefore, we examined the association of APOE4 and various PRSs, based on training sets that utilized differing AD definitions, with incident AD and all-cause dementia (ACD) within 17 years, and with levels of phosphorylated tau181 (P-tau181), neurofilament light (NfL), and glial fibrillary acidic protein (GFAP) in blood. Secondarily, effect modification by APOE4 status and sex was examined.